Firm exit during recessions - Joao Ayres; Gajendran Raveendranathan (Inter-American Development Bank (IDB), 2020)
We analyze a general equilibrium model of firm dynamics to study the effects of shocks to productivity, labor wedge, and collateral constraint (credit shock) on firm exit. We find that only the credit shock increases firm exit. This result is robust to the magnitude of shocks and different model specifications. Calibrating the model to match the behavior of output, employment, and firm debt during the Great Recession (2007-2009) in the United States, we find that the credit shock accounts for the observed rise in firm exit and its concentration among young firms. Furthermore, it accounts for 20 percent of the drop in output and employment.
Keywords: D21; D22; E24; E32; 330; Credit; Firm dynamics; General equilibrium model; Output; Employment